Polymeric Nanoparticles in Oncology: Design, Development and Characterization - Gurav, Sonali; Sharma, Anshu; Shinde, Sunita; Rathod, Raju (Journal of Neonatal Surgery, 2025)
Non-small cell lung cancer (NSCLC) treatment is often limited by the poor aqueous solubility and systemic side effects of Erlotinib, an EGFR inhibitor. To overcome these challenges, this study explores the use of β-Cyclodextrin (BCD), a natural polymer, for the development of biodegradable polymeric nanoparticles to enhance drug solubility, bioavailability, and therapeutic efficacy. Erlotinib-loaded BCD-based nanoparticles were formulated using High-Pressure Homogenization (HPH) and characterized for particle size, polydispersity index (PDI), zeta potential, drug encapsulation efficiency, and in vitro drug release kinetics. Additionally, their cytotoxicity against NSCLC cell lines, biocompatibility, and pharmacokinetic behavior were evaluated. The optimized formulation (Batch B10) demonstrated high drug encapsulation efficiency, controlled and sustained release, and enhanced solubility due to the inclusion of BCD. The nanoparticles exhibited suitable physicochemical properties for targeted delivery, with improved stability and dissolution behavior. In vivo pharmacokinetic studies confirmed a significant increase in bioavailability, with Batch B10 showing superior systemic absorption compared to pure Erlotinib. The study confirms that BCD, a natural polymer, plays a crucial role in enhancing Erlotinib solubility, bioavailability, and therapeutic effectiveness. The optimized BCD-based nanoparticles offer a promising strategy for improving NSCLC treatment while potentially reducing dose-related side effects.